The dynamics of beltramized flows and its relation with the Kelvin waves - González, R. (2011)
We define the beltramized flow as the sum of an uniform translation and an uniform rotation with a Beltrami flow. Some of their features are studied by solving the Euler equations, for different geometries, taking into account the boundary conditions, and for different symmetries. We show that the Kelvin waves are beltramized flows. Finally, we show that the variational principle found in a previous work, remains valid for the beltramized flow.